Monitoring of Ovarian Follicular Development and Ovulation with Transvaginal Sonography (TVS) in Infertile Women in Eastern Region of Nepal - Bhattarai, Manoj (Journal of Nobel Medical College, 2016)
Background Ultrasonography is the first line imaging modality for evaluation of ovaries, monitoring ovarian follicular development and detecting ovulation in infertile women; thus plays a significant role in infertility management. This study was undertaken to evaluate the pattern of ovarian follicular growth and to predict and detect ovulation in infertile women by transvaginal sonography in eastern region of Nepal. Material and Methods Hospital based prospective cross-sectional study on 100 infertile patients referred for ultrasonographic monitoring of ovarian follicle was conducted over duration of 26 months. Serial transvaginal sonography of the patients was performed using standard procedure daily from day 10 of menstrual cycle till detection of ovulation. Identification of ovarian dominant follicle, monitoring of dominant follicle development and detection of ovulation was assessed in relation to the day of menstrual cycle. Results Increase in mean diameter of the dominant follicle was seen in serial ultrasound scan till ovulation, which occurred in all cases by day 16 of menstrual cycle. The average daily follicular growth rate ± SD from day 10 of menstrual cycle till detection of ovulation was 2.2 ± 0.2 mm per day and the mean diameter ± SD of dominant follicle on the day prior to ovulation was 21.4 ± 2.8 mm (range: 17.2 – 26.3 mm). Conclusion Transvaginal sonography is an excellent method for monitoring of ovarian follicular development and shows a linear increase in mean diameter of dominant follicle from day 10 of menstrual cycle till detection of ovulation. Journal of Nobel Medical College Volume 5, Number 1, Issue 8, January-July 2016, 43-48